Digital Islamic Economy Based on Maslahah Mursalah: Implications for Law, Regulation, and the Sustainability of the Halal Industry - Mohamad Ghozali; Wartoyo Wartoyo; Iqbal Noor; Anggara Disuma; Joni (Amwaluna: Jurnal Ekonomi dan Keuangan Syariah, 2026)
This study develops a Maslahah Mursalah-based conceptual framework to strengthen Sharia-compliant digital governance and halal industry sustainability. Using a qualitative normative-juridical and comparative approach, the research examines how Islamic legal principles operate within the digital regulatory systems of Indonesia, Malaysia, and the United Arab Emirates (UAE). The findings reveal that Maslahah Mursalah functions not merely as a supplementary legal argument but as a regulatory philosophy that bridges classical jurisprudence and modern digital governance. Indonesia represents a hybrid dual-authority model, Malaysia demonstrates centralized institutional integration, and the UAE applies a policy-driven innovation approach. Synthesizing these findings, the study formulates a three-dimensional model—normative (legal legitimacy), institutional (governance coordination), and practical (sustainability implementation)—that promotes coherence between Sharia ethics, regulation, and technological advancement. The research contributes to Islamic legal scholarship by repositioning Maslahah Mursalah as a proactive tool for adaptive digital regulation and provides policy recommendations for harmonizing transnational Sharia digital governance frameworks. The study concludes that embedding Maslahah-based ethics within digital transformation is vital for achieving inclusive, transparent, and sustainable halal economic systems.